1993
DOI: 10.1128/iai.61.9.3981-3984.1993
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of immunity to oral challenge with virulent salmonellae in innately susceptible BALB/c mice requires both immune serum and T cells

Abstract: The mechanisms of immunity to salmonellae conferred by immunization with live vaccines were studied by adoptive transfer using the mouse-virulent strain Salnonella typhimurium C5 and innately susceptible BALB/c (by) mice. This organism cannot establish a sublethal infection in naive BALB/c mice. Animals immunized 2 to 3 months earlier with the S. typhimurium SL3261 aroA live vaccine were used as donors of serum, spleen cells, and mesenteric lymph node cells for naive recipients which were challenged orally wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(92 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…[17][18][19][20][21][22][23] Immunoglobulin G antibodies, in addition to T-cell receptor-ab + CD4 + and CD8 + T cells, are essential for resistance against enteric and septicaemic Salmonella diseases in humans and animals. 24 The requirement for systemic antibody responses against such a facultative intracellular pathogen can be explained considering that Summary Several classes and multiple subclasses of immunoglobulins are produced towards protein and polysaccharide antigens in response to Salmonella infection and play a key role in protection against systemic disease. The targeting of Salmonella to Fc receptors (FcR) on phagocytes is a key step in the antibody-mediated antibacterial functions of host cells.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Immunoglobulin G antibodies, in addition to T-cell receptor-ab + CD4 + and CD8 + T cells, are essential for resistance against enteric and septicaemic Salmonella diseases in humans and animals. 24 The requirement for systemic antibody responses against such a facultative intracellular pathogen can be explained considering that Summary Several classes and multiple subclasses of immunoglobulins are produced towards protein and polysaccharide antigens in response to Salmonella infection and play a key role in protection against systemic disease. The targeting of Salmonella to Fc receptors (FcR) on phagocytes is a key step in the antibody-mediated antibacterial functions of host cells.…”
Section: Introductionmentioning
confidence: 99%
“…The crucial role of antibody in host resistance to S. enterica is supported by the observation that the expression of high levels of host resistance against these bacteria requires the presence of immune serum (IS) (anti-S. enterica immunoglobulin) in addition to T-cell-mediated immunity. 23 Antibodies specific for the lipopolysaccharide O-antigen, porins and flagellar epitopes and surface polysaccharides (Vi antigen) have been implicated in serum-mediated protection. 24 Furthermore, vaccines consisting of whole S. enterica or purified bacterial polysaccharide preparations (Vi vaccine), which elicit good anti-S. enterica immunogloblulin responses, but fail to trigger protective T-cell responses, confer a degree of protection against typhoid fever in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Protection against S. typhimurium requires Th1-type immune responses. [22][23][24]43 Moreover, a robust antibody response is known to be required for resistance against virulent Salmonella infection. 22,44,45 Our results demonstrated that, contrary to expectations, paraoxon treatment rendered the animals more resistant to Salmonella infections.…”
Section: Discussionmentioning
confidence: 99%
“…In this animal model, control of the infection requires a robust T helper type 1 (Th1) response as well as neutralizing anti-Salmonella antibodies. [22][23][24] The essential roles of pro-inflammatory cytokines, including IL-12, interferon-c (IFN-c) and TNF-a, in resistance to Salmonella infection in mice as well as in humans is well documented. [25][26][27][28] The present data demonstrate that cholinergic activation of splenic macrophages, through the inhibition of AChE by subchronic exposure to paraoxon, confers enhanced protection against a lethal infection with a virulent strain of S. typhimurium.…”
Section: Introductionmentioning
confidence: 99%